Vulnerability to Poverty in Rural Malawi - Mccarthy, Nancy; Brubaker, Josh; de la Fuente, Alejandro (World Bank, Washington, DC, 2016)
Considerations of risk and vulnerability are key to understanding the dynamics of poverty in rural Malawi. This study measures vulnerability to consumption shortfalls and analyzes its sources using a two-period panel of 2,789 households, drawn from the 2010 Third Integrated Household Survey and the 2013 Integrated Household Panel Survey. The results show that in 2010 two-fifths of all households had a chance of at least 40 percent of falling below the poverty line in the future. The results show that many households in rural Malawi are vulnerable to poverty, although, as with many other studies of rural areas in other countries, much of the vulnerability is caused by chronic poverty. Nonetheless, risks, particularly rainfall and loss of off-farm employment, are also important in explaining why poor households remain poor, and why some non-poor households are more likely to fall into poverty in the next period. Household wealth and agricultural assets can protect households from falling into poverty and reduce the severity of the fall when shocks occur. However, there is little evidence to suggest that other strategies to reduce vulnerability are effective.